European surveillance of antimicrobial resistance in Neisseria gonorrhoeae. Issue 6 (12th October 2010) - Cole, Michelle J; Chisholm, Stephanie A; Hoffmann, Steen; Stary, Angelika; Lowndes, Catherine M; Ison, Catherine A; ,
Abstract : Objective: To perform a European sentinel surveillance study for antimicrobial resistance (AMR) in Neisseria gonorrhoeae as part of the European Surveillance of Sexually Transmitted Infections Programme. Methods: From 2006 to 2008 17 countries participated in the AMR surveillance programme. The susceptibility of a total of 3528 consecutive isolates was tested using the agar dilution breakpoint technique or Etests for ciprofloxacin, penicillin, tetracycline, azithromycin, spectinomycin and ceftriaxone. Nitrocefin was used to detect β-lactamase activity. Results: Rates of resistance to ciprofloxacin, the previously recommended treatment, were high across Europe (42–52%), indicating that usage is no longer appropriate. Although resistance to the currently recommended treatment, ceftriaxone, was not demonstrated, a concerning upward drift in the minimal inhibitory concentration (MIC) distribution was identified since an earlier European study in 2004. No resistance to spectinomycin was seen, whereas azithromycin resistance varied from 2% to 7% and isolates from Scotland (n=4) and Ireland (n=1) showed high-level resistance (MIC >256 mg/l). High-level resistance to tetracycline and penicillin remained relatively constant at 16% and 12%, respectively. Conclusions: AMR is an ongoing problem in Europe, with high rates of resistance to many previously recommended therapeutic agents observed in many European countries. Continual European and global surveillance of AMR in N gonorrhoeae is essential to monitor for increasing, emerging and high-level resistance to therapeutically relevant agents and to inform treatment guidelines so optimum treatments are administered.